Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.inorgchem.9b03640
|View full text |Cite
|
Sign up to set email alerts
|

Potent Inhibition of Thioredoxin Reductase by the Rh Derivatives of Anticancer M(arene/Cp*)(NHC)Cl2Complexes

Abstract: Metal complexes provide a versatile platform to develop novel anticancer pharmacophores, and they form stable compounds with N-heterocyclic carbene (NHC) ligands, some of which have been shown to inhibit the cancer-related selenoenzyme thioredoxin reductase (TrxR). To expand a library of isostructural NHC complexes, we report here the preparation of Rh III -and Ir III (Cp*)(NHC)Cl 2 (Cp* = η 5 -pentamethylcyclopentadienyl) compounds and comparison of their properties to the Ru II -and Os II (cym) analogues (cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 82 publications
0
34
0
3
Order By: Relevance
“…The design of drug candidates based on metal NHC complexes has been dominated by gold and silver as metals, however, more recently, an increasing number of metals has demonstrated very promising results, including, for example, rhodium [ 8 , 9 , 10 , 11 , 12 ] and iridium [ 12 , 13 ] species.…”
Section: Introductionmentioning
confidence: 99%
“…The design of drug candidates based on metal NHC complexes has been dominated by gold and silver as metals, however, more recently, an increasing number of metals has demonstrated very promising results, including, for example, rhodium [ 8 , 9 , 10 , 11 , 12 ] and iridium [ 12 , 13 ] species.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly highlighted in the case of the ansa ferrocidiphenol, 27, which is one of the most cytotoxic complexes on cancer cells (IC 50 = 0.089 µM), whereas its quinone methide, 28, is only an average inhibitor of TrxR (IC 50 = 0.15 µM). This lack of correlation has previously been found in other systems, such as NHC-gold complexes [72,73]. In addition, it has been shown that, in cancer cells, 8 the QM derived from the monophenol complex 3, is transformed into the indene 36a via the rearrangement process depicted in Scheme 12 [42].…”
Section: Scheme 19mentioning
confidence: 72%
“…Complex 5 also kills cancer cells by ROS-mediated apoptosis by targeting TrxR, and it further improves compatibility in animal models [ 37 ]. Next, rhodium complexes are also a large class of conventional TrxR inhibitors, such as rhodium(I) complex 6 and rhodium(III) complex 7 [ 78 , 79 ], all of which can kill cancer cells by TrxR-inhibition-mediated ROS regulation ( Figure 3 A). Recently, Chen et al also found that a novel triphenylphosphonium-modified terpyridine platinum(II) complex ( 8 ) is an inhibitor of mitochondrial TxrR with enhancement of caspase-3-independent apoptosis by increasing cellular ROS [ 80 ].…”
Section: Anti-cancer Metal Complexes Inhibiting Antioxidant Enzymesmentioning
confidence: 99%
“…Contributions from the Ott group, Chen group, Shahraki group, and others have greatly enriched the entry of metal complexes targeting the antioxidant enzyme system as promising anti-cancer agents [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. Despite the importance of metal complexes as antioxidant enzyme inhibitors, no clinical anti-cancer drug targets TrxR, CAT, or Prx currently, which may be due to several major challenges in the field.…”
Section: Anti-cancer Metal Complexes Inhibiting Antioxidant Enzymesmentioning
confidence: 99%